Indian older adults and the digit span A preliminary report - Ravikesh Tripathi; Keshav Kumar; Srikala Bharath; Marimuthu P; Vikram Singh Rawat; Mathew Varghese (Dementia & Neuropsychologia)
ABSTRACT. The digit span test is widely used to assess attention and working memory. It is a portable, relatively culture-free and frequently used test. However, the cultural validity of this test, particularly in the Indian older population, is not well established. Objective: This study explores the usefulness of the digit span test for Indian older adults with different levels of education. Methods: Two hundred and fifty-eight community-dwelling healthy normal older adults formed the sample of this study. All study participants were screened using a semi-structured interview schedule, the modified MINI Screen, the Indian version of the Mini-Mental State Examination, a measure of activities of daily living and the digit span test administered verbally. Results: The results indicated that participants with higher educational level performed significantly better than low-educated participants on the digit span test. Participants with low education often struggled with the digit span test and resorted to guessing the digits. Conclusion: Our study clearly demonstrates that the digit span test can be useful for educated participants. However, its usefulness and ecological validity is questionable for those with low education and low literacy, warranting future research.